Iceland in the European Union: Will it ever happen? EUMA Papers, Vol. 4, No. 19, September 2007 - Gudjonsdottir, Vilborg Asa. (2007)
[Introduction]. Relations between Iceland and the European Union date back to 1973 when Iceland signed a bilateral free trade agreement with the EU. The agreement only covered part of the trade between Iceland and EU member states at that time, and after the EU set forth the Single European Act1 in 1986 the bilateral agreement was replaced by the European Economic Area Agreement (EEA), to prevent trade barriers between EFTA2 countries and EU member states. The main goal of the EEA Agreement is to form a homogeneous market zone covering EU and EFTA member states Iceland, Norway and Liechtenstein. Besides giving Iceland open access to EU´s common market the agreement also includes common rules in various areas to ensure fair competition, environmental protection, consumer protection and minimum social benefits. In addition the three EFTA states can participate in EU´s framework programmes, on research and development, education, information services, social policy, the environment and the audio-visual sector.3 Although the EEA agreement does not cover agriculture and fisheries, Iceland has bilateral agreements with the EU covering trade with agricultural and fisheries products. In addition the EEA agreement does not cover other aspects of the European Union, such as foreign affairs, the economic and monetary union, customs union, justice and home affairs, wildlife conservation and utilization of natural resources.4 Talks of EU membership have been adherent in Iceland for quite some time. Why hasn´t Iceland joined the European Union, and what are the chances of it doing so in the nearest future?